Catalytic Performance of Cu-Ni supported on Rice Husk Ash-derived SiO2 for the Hydrogenation of Ethylene Carbonate to Ethylene Glycol - Maharani, Najiah Sephia; Rahmawati, Novia Dwi; Aziz, Isalmi; Maryati, Yati; Agustian, Egi; Widjaya, Robert Ronal; Yati, Indri; Prasetyo, Joni; Rinaldi, Nino; Dwiatmoko, Adid Adep (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
Ethylene glycol, a crucial compound extensively utilized in solvents, coolants, antifreeze, polyester fiber production, and as a natural gas-drying agent, can be synthesized via the hydrogenation of ethylene carbonate. In this study, the synthesis, characterization, and catalytic performance of Cu-Ni/SiO2 catalysts for this reaction, utilizing silica (SiO2) derived from rice husk ash, were investigated. Silica was impregnated with copper (Cu) and nickel (Ni) by varying the weight ratio (Cu:Ni = 10, 7:3, 3:7, 10) to prepare bimetallic catalysts. X-ray Diffraction (XRD) analysis confirmed the presence of both Cu and Ni phases in all the catalysts. The 3Cu7Ni/SiO2 catalyst displayed the lowest reduction temperature and the largest surface area (257.97 m²/g). The 7Cu3Ni/SiO2 catalyst exhibited the highest acidity (1.91 mmol/g) and superior metal dispersion, as confirmed by the Field Emission Scanning Electron Microscopy - Energy Dispersive X-Ray (FE-SEM-EDX) analysis. Catalytic activity was evaluated in a batch reactor under 40 bar H2 pressure at 150 °C for 3 h with a catalyst-to-ethylene carbonate ratio of 5:1. Among the catalysts examined, the 7Cu-3Ni/SiO2 composition demonstrated the highest catalytic performance, achieving 15.14% conversion of ethylene carbonate and 80.51% selectivity towards ethylene glycol. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).